Fergana Valley Rural Population Metal Handicrafts - Ziyod Esonov (Genius Journals, 2021)
This article discusses the development of blacksmithing, knife-making, degreasing and coppersmithing in the Uzbek, Tajik and Uyghur villages of the Fergana Valley, as well as the ethno-territorial features of rural handicraft centers and products, methods of preparation
Keywords: Fergana Valley; metallurgical industries; development factors; rural centers